Crop Assurance Strategies for Irrigated Grain Sorghum Production - F. R. Lamm (Kansas Agricultural Experiment Station Research Reports, 2022)
This sprinkler-irrigated study was conducted from 2018 to 2021 at the Kansas State University Northwest Research-Extension Center near Colby, KS, to evaluate four different water management strategies that could provide assurance of adequateyielding grain sorghum. The grain sorghum was grown on sites with good initial soil water at planting (>70% of field capacity within the 8-ft deep silt loam profile). Strategies were 1) No seasonal irrigation; 2) Irrigation of 100% of ET minus Rain after the boot stage through remainder of season; 3) Irrigation of 100% of ET minus Rain up to a limit of 6 inches; and 4) Irrigation of 100% of ET minus Rain up to a limit of 3 inches. Cropping season rainfall ranged from 5.48 inches to 13.98 inches and irrigation ranged from 0 to 11 inches across strategies for the 4 years of the study. Yield increases due to irrigation varied across years, ranging from -3.6 bu/a to 21.2 bu/a, but averaged only 7.2 bu/a over the non-irrigated treatment. Average yields were 138, 143, 144, and 145 bu/a for the four respective water management strategies. Soil water extraction by the grain sorghum was greater in the drier years and increased with less applied irrigation. These results indicate that adequately-yielding grain sorghum can be produced on sites with good soil water profiles at planting with little (≈ 3 inches) or even no in-season irrigation.
Keywords: crop assurance; grain sorghum; sorghum strategy; sorghum yield